CONCEPTUAL BASES FOR THE DEVELOPMENT OF HOTEL & RESTAURANT AND RESORT & RECREATIONAL INFRASTRUCTURE OF THE OIL & GAS COMPLEX - Kis, S. Y.; Gumenyuk, V. V.; Kis, G. R.; Hrechanik, B. V. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The article deals with the problems of the functioning of hotel & restaurant and resort & recreational infrastructure objects, which are subordinated to the domestic enterprises of the oil and gas complex. The emphasis is placed on the fact that in the sphere of management of Ukrainian oil and gas enterprises with full or predominant share of state property there are sanatoriums, recreation centers, hotels and health improving complexes, the main task of which is to organize services of accommodation, meals, rest, treatment and rehabilitation of workers. As a result of conducted research with using the objective characteristics of sectoral infrastructure services, the expert survey identified the main problems of their operation in market conditions, which are mainly related to the high degree of depreciation of the passive part of fixed assets and the shortage of personnel whose professional qualifications meets the needs of the institution and the requirements of a competitive market environment. In order to increase the efficiency of using the hotel & restaurant and resort & recreational infrastructure potential of the domestic oil and gas complex, the priority measures related to the necessity of forming a substrategy of the development of service sector objects with an emphasis on the development of their human resources are proposed.